The Ifugao Living Law - Barrameda, Mary Constancy (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2008)
The legacy of colonial rule is intolerance for indigenization. Having lived the "western" way of life, Filipinos, particularly the Filipino elites subscribe to a system of laws that is culturally misplaced. The effects of religious and consumer values have been devastating and often irreversible even for indigenous peoples (IPs) who live in near isolation. The author suggests that a path to nationhood can be led by the IPs of the Philippines. Relatively untouched by Spanish or American influences, IPs govern themselves with indigenous laws dating back to centuries before the arrival of the first Spaniard. With preserved cultures, the peoples of the Cordilleras have settled disputes without the aid of codified western legal references and have not gone extinct. It is a body of knowledge that needs to be shared by the IPs and studied by scholars. Much can be learned from IPs and their laws and an open mind could free Filipinos from the mindset that only western ideas are good.
Keywords: Indigenous Peoples; Ifugao